1995
DOI: 10.1002/jmor.1052240204
|View full text |Cite
|
Sign up to set email alerts
|

Early embryonic development, including germ‐disk stage, in the theridiid spider Achaearanea japonica (Bös. et Str.)

Abstract: Early embryonic development, from the first cleavage to the germ-disk stage, in the theridiid spider Achaearanea japonica was examined by light and electron microscopy. The eggs are syncytial during the first four cleavages, and then invaginations of cell membranes fuse to generate the blastomeres at the sixteen-nucleus stage. The cleavage pattern is a modified type of total cleavage. It appears that radial bundles of microtubules that radiate from the perinuclear cytoplasm may participate in the migration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 13 publications
1
28
0
Order By: Relevance
“…Also, the staging systems previously provided for early stages of P. tepidariorum (Akiyama- Oda 2003, 2006;up to 60 h;Yamazaki et al 2005;Kanayama et al 2010) as well as the staging through approximately half of the development (McGregor et al 2008) were reassessed and emended. Furthermore, the precise description of early cleavage stages of the closely related species Achaearanea japonica (Suzuki and Kondo 1995) was taken into account. As P. tepidariorum develops nearly twice as fast as C. salei and the developmental stages of both species are not duplicates, we defined several new stages by focussing on developing organ systems (e.g.…”
Section: Embryonic Stagesmentioning
confidence: 99%
“…Also, the staging systems previously provided for early stages of P. tepidariorum (Akiyama- Oda 2003, 2006;up to 60 h;Yamazaki et al 2005;Kanayama et al 2010) as well as the staging through approximately half of the development (McGregor et al 2008) were reassessed and emended. Furthermore, the precise description of early cleavage stages of the closely related species Achaearanea japonica (Suzuki and Kondo 1995) was taken into account. As P. tepidariorum develops nearly twice as fast as C. salei and the developmental stages of both species are not duplicates, we defined several new stages by focussing on developing organ systems (e.g.…”
Section: Embryonic Stagesmentioning
confidence: 99%
“…By contrast, our previous and present studies with the spider Achaearanea highlight the importance of cell-cell communication mediated by Dpp and Sog in dorsoventral patterning (Akiyama- Oda and Oda, 2006) and by Delta-Notch signaling in mesoderm and caudal specification. The necessity for cell-cell communication in early spider embryos may be due to early completion of cellularization (Kondo, 1969;Suzuki and Kondo, 1995). Based on Achaearanea studies, the blastopore region is particularly important, because cells producing Dpp signals originate from that region and progressive activation of Delta-Notch signaling starts there.…”
Section: Evolution Of Early Patterning In Arthropodsmentioning
confidence: 99%
“…The energids give rise to a germ disc of relatively uniform epithelial cells. Although when the cellularization is completed in the species used has not been examined, a previous work on a closely related spider species, Achaearanea japonica, showed that every nucleus was already enclosed with plasma membrane at the 16-blastomere stage (Suzuki and Kondo, 1995). At the center of the germ disc, a white spot is seen (Fig.…”
Section: Early Embryogenesis Of Achaearanea Tepidariorummentioning
confidence: 99%